2021
DOI: 10.1111/nin.12474
|View full text |Cite
|
Sign up to set email alerts
|

Institutional procedural discrimination, institutional racism, and other institutional discrimination: A nursing research example

Abstract: Institutional discrimination matters. The purpose of this longitudinal communitybased participatory research study was to examine institutional procedural discrimination, institutional racism, and other institutional discrimination, and their relationships with participants' health during a maternal and child health program in a municipal initiative. Twenty participants from nine multilingual, multicultural community-based organizations were included. Overall reported incidences of institutional procedural dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
(59 reference statements)
1
12
0
Order By: Relevance
“…Study participants were required to use the NIRN model to develop their home‐based programmes and they reported that the use of the mainstream Western implementation model and scientific process for capacity building did not fit their thinking processes (Parker et al, In review; Lim et al, 2022). This resulted in more participants reporting that the meetings and materials presented were based on Western culture, so more people had difficulty understanding the work in November (65%, n = 11) than in April (47%, n = 8) (Lim et al, 2022). These findings are consistent with a previous study that the NIRN model provided a programme implementation framework, however, it was very complex, resource intensive and the language developed for the educational system did not fit well in healthcare (Brémault‐Phillips et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Study participants were required to use the NIRN model to develop their home‐based programmes and they reported that the use of the mainstream Western implementation model and scientific process for capacity building did not fit their thinking processes (Parker et al, In review; Lim et al, 2022). This resulted in more participants reporting that the meetings and materials presented were based on Western culture, so more people had difficulty understanding the work in November (65%, n = 11) than in April (47%, n = 8) (Lim et al, 2022). These findings are consistent with a previous study that the NIRN model provided a programme implementation framework, however, it was very complex, resource intensive and the language developed for the educational system did not fit well in healthcare (Brémault‐Phillips et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Participants' regular and contract work continuously accumulated. Not giving enough time to develop a useable home‐based programme can be viewed as institutional procedural discrimination (Lim et al, 2022). So, it is not surprising that there were no statistical changes in implementation processes outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations